Assessment Instruments of Caring Attitudes and Science Knowledge Competencies IV Grade Elementary School Student - Dewi, Luh Gede Ayu Rusiana; Gunamantha, I Made; Wibawa, I Made Citra (Journal for Lesson and Learning Studies, 2022)
The attitude of students' concern for the surrounding environment is still relatively low, this is due to the lack of use of assessment instruments in assessing student attitudes. The purpose of this study is to analyses the design and tests the feasibility of the instrument of caring attitude and science knowledge competence. This research belongs to the type of development research, using the ADDIE development model. The subjects involved in this study were 2 lecturers and 3 fourth grade elementary school teachers. Data was collected using field study, observation, questionnaire, and test methods. The data obtained in the study were then analyzed by testing the validity and reliability of the instrument. The results of data analysis showed that the validation obtained an average percentage for the content aspect of 76.67% (adequate), the aspect of the social science technology model 80% (adequate), the format aspect 82% (very feasible), the language aspect 93% (very feasible) and 82% presentation aspect (very decent). Furthermore, the reliability test showed the results of the reliability coefficient values ​​for the test instrument and the questionnaire instrument were 0.893 and 0.939, respectively. This value is in the range of 0.80 < r 1.00, this shows that the reliability of the two instruments used in this study is very high. Based on these results, it can be concluded that the assessment instrument for caring attitudes and science knowledge competencies are valid and reliable category so that it is very feasible to be developed and used in the learning process.